Analiza oddziaływania na środowisko planowanej eksploatacji kruszywa w miejscowości Łaz = Environmental impact assessment of the planned open pit stone mine in Łaz - Kołodziejczyk, Urszula; Kostecki, Jakub; Wasylewicz, Róża (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The development of society depends on environmental resources, which can be divided into renewable and non-renewable. The last group includes minerals such as oil, coal, and break-stone. The paper presents the environmental impact assessment of the planned open-pit stone mine in Łaz, conditions for the location of the break-stone open pit mine in Łaz, Lubuskie Province.
Keywords: oddziaływanie inwestycji na środowisko; kruszywo; uwarunkowania eksploatacji; environmental impact assessment; stone mine; environmental conditions